MIRERC 068/2025: Assessment of the Effectiveness of Community Health Promoters in Hypertension Care in Imenti North Sub-County - Mukundi, Vincent; Dr. Ananias Njagi Nkonge; Dr. Elias Kinoti, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
This study aims to assess the effectiveness of Community Health Promoters (CHPs) in hypertension care by examining the availability and utilization of resources, support for treatment adherence, and the challenges CHPs face in Imenti North Sub County. Limited documentation and research in this region have created a critical knowledge gap regarding the contribution of CHPs to hypertension management. A descriptive survey design will be employed, targeting CHPs in Imenti North Sub County. CHPs will be selected through simple random sampling for participation in the study. Data will be gathered using a structured questionnaire, and the collected data will be analyzed using SPSS, employing descriptive and inferential statistics to address the research objectives. This study will identify gaps in the current role of CHPs in hypertension care, offering insights into areas for improvement and providing recommendations to enhance their effectiveness. By addressing these gaps, the research aims to strengthen healthcare delivery in Imenti North Sub County and potentially inform policy and practice in similar regions.